If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 4x + 7n + -6x + 4n Reorder the terms: 0 = 7n + 4n + 4x + -6x Combine like terms: 7n + 4n = 11n 0 = 11n + 4x + -6x Combine like terms: 4x + -6x = -2x 0 = 11n + -2x Solving 0 = 11n + -2x Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11n' to each side of the equation. 0 + -11n = 11n + -11n + -2x Remove the zero: -11n = 11n + -11n + -2x Combine like terms: 11n + -11n = 0 -11n = 0 + -2x -11n = -2x Divide each side by '-11'. n = 0.1818181818x Simplifying n = 0.1818181818x
| 285.3736=2*3.14*r^2+2*3.14*r*5.3 | | 3lnx=2-lnx | | -2.6=3.3-x | | 4(3x-6)-4n=16 | | 87(43)= | | 4v+2v=12 | | 30m+50=20m+100 | | x/5-4=10x-4 | | y=108+16(12) | | 8y+(-2)=22 | | (2x+6)+(5x+4)= | | 7r^2+20r-3=0 | | 8x+6=7x-9 | | 2x+10=-2-4x | | -6z-11=61 | | 20x-16x-160=30x+360 | | y=108+16(11) | | 2X+457= | | 5*(2x-11+17)=52 | | 50-3x=30 | | log1024/5√3 | | 3p-15+(-3p)=-27 | | (4x+1)(7-3x)=0 | | -y^2+2y+x+2=0 | | (5a+3)=14a-29 | | -0.5x+2y=2 | | (1/3)9cu | | 5/7:15/14=6/5 | | ax-by=2 | | -12X+7X=13 | | -3r*4rx+x+12= | | -5=C-10 |